The Gut-Brain Axis in Type 2 Diabetes: A Review of Microbial Mechanisms and Clinical Implications - Goenadi , Emmanuel Adrian; Pramudito, Ignatius Aditya Haryo; Saputra, Petra Heinson Handoyo; Bararinda, Pradipta Putramachristy; Priskila, Loury (PT Dexa Medica, 2025)
The understanding of Type 2 Diabetes Mellitus (T2DM) is evolving beyond traditional risk factors to recognize the Gut Microbiota (GM) as a pivotal player in its pathogenesis. This narrative review illuminates the critical role of the Gut-Brain Axis (GBA), detailing how microbial dysbiosis—characterized by a loss of butyrate-producing bacteria—drives the systemic inflammation and insulin resistance central to T2DM. This paper provides an overview of microbiota-based interventions (probiotics, prebiotics, FMT) and explore the synergistic impact of physical activity, which not only enhances insulin sensitivity but also beneficially modulates the GM. The evidence indicates that an integrated approach, combining targeted microbial modulation with regular physical activity, represents a powerful therapeutic strategy for improving glucose homeostasis in T2DM.